Pengaruh Media Augmented Reality (AR) Terhadap Kemampuan Mengenal Huruf Vokal pada Anak Usia Dini - Fina Sindy Alfani (ABNA : Journal of Islamic Early Childhood Education, 2020)
The problem in this study is the ability to recognize vowels in children is still low. Inadequate selection of media, teacher creativity in utilizing learning media also affects the ability to recognize vowels in children. The objectives of this study are (1) To find out how high the ability to recognize vowels in children aged 3-4 years using augmented reality media in PAUD Islam MakarimaKartasura 2019/2020 Academic Year (2) To find out how high the ability to recognize vowels in children age 3-4 years using the Image Card media in Islamic PAUD MakarimaKartasura 2019/2020 Academic Year (3) To find out the difference in the ability to recognize vowels between those using augmented reality media with the picture card media in 3-4 year old children in Islamic PAUD MakarimaKartasura Academic Year 2019/2020. This study uses a quantitative experimental research type, carried out in Islamic Makarima PAUD in September 2019 - April 2020. The population in this study is all children in the playgroup (KB). By taking a sample of 48 children. The results of this study indicate that with augmented reality media get an average value of 30.5.